The Differential Expression of Sucrose Synthase in Relation to Diverse Patterns of Carbon Partitioning in Developing Cotton Seed. - Ruan, Y. L. (1997)
Developing cotton (Gossypium hirsutum L.) seed exhibits complex patterns of carbon allocation in which incoming sucrose (Suc) is partitioned to three major sinks: the fibers, seed coat, and cotyledons, which synthesize cellulose, starch, and storage proteins or oils, respectively. In this study we investigated the role of Suc synthase (SuSy) in the mobilization of Suc into such sinks. Assessments of SuSy gene expression at various levels led to the surprising conclusion that, in contrast to that found for other plants, SuSy does not appear to play a role in starch synthesis in the cotton seed. However, our demonstration of functional symplastic connections between the phloem-unloading area and the fiber cells, as well as the SuSy expression pattern in fibers, indicates a major role of SuSy in partitioning carbon to fiber cellulose synthesis. SuSy expression is also high in transfer cells of the seed coat facing the cotyledons. Such high levels of SuSy could contribute to the synthesis of the thickened cell walls and to the energy generation for Suc efflux to the seed apoplast. The expression of SuSy in cotyledons also suggests a role in protein and lipid synthesis. In summary, the developing cotton seed provides an excellent example of the diverse roles played by SuSy in carbon metabolism.